Persepsi Konsumen terhadap Narasi Black Campaign: Studi Kualitatif tentang Reputasi Merek Deodoran X di Media Sosial - Syaharani, Pricilla Tirta Ayu; Winduwati, Septia (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
This study analyzed consumer perceptions formed against the Black campaign narrative about deodorant X on social media. Using a qualitative approach through in-depth interviews thematic analysis, observation of the spread of questionnaires, traces of digital analysis on social media. The study linked the findings to theoretical frameworks ELM, source credibility, prosumer theory, negativity bias, and E-WOM. The results show that negative perceptions are primarily formed through repeated exposure to content on platforms such as X (Twitter) and TikTok. Consumers with no usage experience are more receptive to negative narratives because they rely on peripheral cues, whereas experienced users tend to reject issues through more critical evaluation. Communicator credibility, negative E-WOM, and social proof strengthen the formation of public opinion, especially in vulnerable consumer groups. These findings confirm the perception of the black campaign is a social construct that is influenced by the interaction between platform algorithms, source credibility, and personal experience. Consumers without experience are more easily affected, while experienced users are more critical. Perception arises from the interaction of algorithms, message sources, and personal experiences. Penelitian ini menganalisis persepsi konsumen terbentuk terhadap narasi black campaign mengenai Deodoran X di media sosial. Menggunakan pendekatan studi kasus kualitatif melalui wawancara mendalam, observasi penyebaran kuesioner, jejak analisis digital di media sosial. Penelitian mengaitkan temuan dengan kerangka teori ELM, source credibility, prosumer theory, negativity bias, dan E-WOM. Hasil menunjukkan bahwa persepsi negatif terutama terbentuk melalui paparan konten yang berulang di platform seperti X (Twitter) dan TikTok. Konsumen tanpa pengalaman penggunaan lebih mudah menerima narasi negatif karena mengandalkan isyarat periferal, sedangkan pengguna berpengalaman cenderung menolak isu melalui evaluasi yang lebih kritis. Kredibilitas komunikator, E-WOM negatif, dan social proof memperkuat pembentukan opini publik, terutama pada kelompok konsumen yang rentan. Temuan ini menegaskan persepsi terhadap black campaign merupakan konstruksi sosial yang dipengaruhi interaksi antara algoritma platform, kredibilitas sumber, dan pengalaman personal. Konsumen tanpa pengalaman lebih mudah terpengaruh, sedangkan pengguna berpengalaman lebih kritis. Persepsi muncul dari interaksi algoritma, sumber pesan, dan pengalaman personal.